Latent autoimmune diabetes in adults: a focus on β-cell protection and therapy - Yin, Wenfeng; Luo, Shuoming; Xiao, Zilin; Zhang, Ziwei; Liu, Bingwen; Zhou, Zhiguang (Frontiers in Endocrinology, 2022)
Latent autoimmune diabetes in adults (LADA) is a heterogeneous disease sharing some phenotypic, genetic, and immunological features with both type 1 diabetes and type 2 diabetes. Patients with LADA have a relatively slow autoimmune process and more residual islet β cell function at onset, which facilitates a time window to protect residual islet β cells and delay or inhibit disease progression. It is crucial to figure out various and heterogeneous factors of affecting islet β cell function for precise therapy of LADA patients. In this review, we, firstly, describe the natural history of LADA. Thereafter, we summarize related factors based on islet β cell, including age of onset, body mass index, and lifestyle or environmental factors, genetic background, and immune mechanisms. In parallel, we evaluate the impact of current hypoglycemic agents and immune intervention therapies for islet β cell protection. Finally, we discuss the opportunities and challenges of LADA treatment from the perspective of islet function protection.